Alstoscholarisines F and G, two unusual monoterpenoid indole alkaloids from the leaves of Alstonia scholaris. Issue 48 (2nd December 2015) - Yang, Xing-Wei; Song, Chang-Wei; Zhang, Yu; Khan, Afsar; Jiang, Li-Ping; Chen, Yong-Bin; Liu, Ya-Ping; Luo, Xiao-Dong
Graphical abstract: Abstract: Alstoscholarisine F (1 ), a monoterpenoid indole alkaloid pigment with unprecedented carbon skeleton, and alstoscholarisine G (2 ) incorporated with a third nitrogen atom were isolated from the long-term stored leaves of Alstonia scholaris . Their structures were established by extensive MS and NMR spectroscopic analysis and the absolute configuration of1 was defined by comparison of experimental and calculated ECDs. Compounds1 and2 were subjected to hippocampal neuronal stem cells (NSCs) proliferation evaluation, but they did not show significant effect.